What is the training? (Docentes 2.0 Journal, 2018)
This magazine aims to support students, so that they develop their own method of study and thus exploit their full potential, obtaining good academic results and successfully pursuing their career. The management of human talent as part of the administration, is established as an axis where management must be thought beyond the internal human resource. It is to give a turn to the management that constitutes an end as such and not a means for economic purposes in favor of the profitability of a few.
Keywords: training; education; management